In vitro culture of Echinococcus multilocularis producing protoscoleces and mouse infection with the cultured vesicles. Issue 1 (December 2016) - Wang, Hui; Li, Jun; Guo, Baoping; Zhao, Li; Zhang, Zhuangzhi; McManus, Donald; Wen, Hao; Zhang, Wenbao
Abstract Background Alveolar echinococcosis (AE) is a lethal zoonosis caused by the fox-tapewormEchinococcus multilocularis . The disease is difficult to treat and an effective therapeutic drug is urgently needed. Reliable models are essential for drug development. In this study, we developed both in vitro and in vivo models of larvalE. multilocularis . Results The protoscoleces (PSC) ofE. multilocularis from jirds were successfully cultured in a modified RPMI1640 based medium containing 25 % (v/v) fetal bovine serum (FBS). After 100 days of culture, PSC developed to larval vesicles (small unilocular cysts) and the fast growing vesicles produced PSC in brood capsules. In addition, mice were intraperitoneally injected with 30 cultured small vesicles and 100 % of the mice had resulting metacestode masses. Conclusions Larval protoscoleces and vesicles ofE. multilocularis grow healthily in vitro in the RPMI1640 based medium containing 25 % FBS.Echinococcus multilocularis in vitro and in vivo models provide a valuable platform for investigating the biology of the parasite and screening effective therapeutic drugs against AE.